SANDEQ FESTIVAL AS A FORM OF CULTURE WEST SULAWESI MARITIME COMMUNITY - Hastira , Muhammad Fajhriyadi; Darwis , Ananda Ashani Fitriani (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal